The Role of high-dose vitamin D supplementation on disease severity and lipid profile in psoriatic patients - a pilot study - Prtina, Alma; Grabež, Milkica; Vujnić, Milorad; Rašeta Simović, Nela (Scripta Medica, 2020)
Background/Aim: Psoriasis is a chronic inflammatory skin disease that is associated with a higher prevalence of cardiovascular (CV) risk factors. The effect of vitamin D on bone health has been long known, but its extraskeletal role especially in cardiovascular disease and skin disease, is the subject of recent research. This study aimed to assess the influence of high-dose vitamin D supplementation on the Psoriasis Area and Severity Index (PASI) score and lipid profile in patients with psoriasis.Methods: The study included 20 adult patients with chronic plaque psoriasis. They received vitamin D capsules in a daily dose of 5,000 IU over 12 weeks. Measured serum concentrations of lipid metabolism parameters were triglycerides (TG), total cholesterol (TC), low-density lipoproteins (LDL) and high-density lipoproteins (HDL). PASI was used to determine the severity of the disease.Results: High-doses vitamin D supplementation had a significant influence on reduction in PASI score in all patients (17.99 ± 12.42 vs 10.27 ± 8.53; p < 0.001). The supplementation of high dose vitamin D induced statistically significant lowering of the TC, LDL-C and TG in the psoriatic patients (p < 0.05). Furthermore, significant increase in serum HDL-C level was observed. The change of PASI score showed week positive correlation with the changes in serum TC and LDL-C (r = 0.303, p = 0.03 and r = 0.357 p = 0.013).Conclusion: High-dose vitamin D supplementation had a positive impact on clinical status of the chronic plaque psoriasis patients, measured by PASI score. It also improved the serum lipid profile of these patients. Double-blinded prospective studies are needed in order to get more comprehensive data related to vitamin D, lipid metabolism and severity of psoriasis.
Keywords: Psoriasis; Disease severity; Lipid profile; High-dose; Vitamin D